DETEKSI SPORA DI UDARA PADA PERMACULTURE AREA DI BUKIT KOR TERENGGANU MALAYSIA - Rizkina, Setia Azzahra; Fitria, Fitria; Suprianto, Andi Agus; Mohamed Sidique, Siti Nordahliawate (Fakultas Pertanian, Universitas Janabadra, 2024)
permaculture has the principle of balance and sustainability. The growth of microbes or spores can be detrimental to plants even if the ecosystem and environment are healthy and good, such as a permaculture area. The spread of plant diseases is often caused by spores spread through the air. The aim of this research is to determine the distribution of spores in the air in the Kor Hill permaculture area. Observations of spore samples were carried out in September 2023 at the Kor Hill Agricultural Complex laboratory, Marang, Terengganu, Malaysia at a height of 35 meters above sea level. This research used the Completely Randomized Design (CRD) method. The research results showed that the spore colony samples observed were groups of fungi known as sterile hyphae or sterile mycelia. Sterile hyphae or sterile mycelia are a type of fungus that does not produce reproductive structures, either through sexual or asexual reproduction.